До проблеми визначення поняття та видів суб’єктів державного регулювання в агропромисловій сфері - Дегтярьова, С. В.; Dehtiarova, S. V. (Науковий вісник публічного та приватного права. - 2019. - Вип. 4, т. 2. - С. 50-55, 2019)
Розглянуто зміст поняття «суб’єкт державного регулювання в агропромисловій сфері» та здійснено їх класифікацію. Визначено, що під суб’єктами державного регулювання в агропромисловій сфері слід розуміти органи державної влади (або суб’єкти недержавного регулювання), які відповідно до норм чинного законодавства України наділені всією необхідною сукупність владних повноважень, що своєю чергою дають їм можливість приймати юридично значущі управлінські рішення, котрі є обов’язковими для виконання об’єктами, на які спрямована їх регулююча діяльність. Наголошено, що регулювання в агропромисловій сфері здійснюється чималою кількістю суб’єктів, які найбільш доцільно поділити на загальнодержавні та спеціалізовані.

In the article, based on the analysis of scientific views of scientists, the content of the concept of "subject of state regulation in the agro-industrial sphere" is defined and their classification is made. It is emphasized that the classification of subjects outlined in the sex is: first, of great theoretical importance because it facilitates scientific research in a particular direction; and second, of practical importance, since it enables the identification of connections between subjects within a particular system. It is substantiated that state regulation in the agro-industrial sphere is carried out by a considerable number of subjects, which are most expedient to be divided into national and specialized ones. It is emphasized that state regulation of the agro-industrial sphere requires the authorized subjects of active activity, and therefore it is most expedient to refer to them as “subjects of legal relations”. It is determined that the subjects of state regulation in the agroindustrial sphere should be understood as bodies of state power (or subjects of non-state regulation), which in accordance with the norms of the current legislation of Ukraine are endowed with all the necessary set of powers, which in turn give them the opportunity to take legally significant managerial decisions that are binding on the entities to which their regulatory activities are directed. It is concluded that regulation in the agro-industrial sphere is carried out by a considerable number of subjects, which are most expedient to be divided into national and specialized ones. It is difficult to overestimate the importance of the efficiency and effectiveness of the activity of each subject of state regulation of the research sphere, since the proper exercise of their powers will allow: First, to provide the population of Ukraine with all the necessary foodstuffs at affordable prices; second, to process raw materials effectively; third, to raise the level of the economy of the country, and as a result to solve all existing problems of economic, political, social, cultural and domestic character. That is why it is so important that the state empowers the above entities: (a) all necessary powers; b) created a quality legal field for their activities; c) provided all the necessary logistical and financial resources for the implementation of state policy in the agro-industrial sphere of Ukraine.

Рассмотрено содержание понятия «субъект государственного регулирования в агропромышленной сфере» и осуществлена ​​их классификация. Определено, что под субъектами государственного регулирования в агропромышленной сфере следует понимать органы государственной власти (или субъекты негосударственного регулирования), которые в соответствии с нормами действующего законодательства Украины наделены всей необходимой совокупностью властных полномочий, которые в свою очередь дают им возможность принимать юридически значимые управленческие. решения, обязательные для выполнения объектами, на которые направлена ​​их регулирующая деятельность. Отмечено, что регулирование в агропромышленной сфере осуществляется немалым количеством субъектов, которые наиболее целесообразно разделить на общегосударственные и специализированные.
Дегтярьова, С. В. До проблеми визначення поняття та видів суб’єктів державного регулювання в агропромисловій сфері / Дегтярьова С. В. // Науковий вісник публічного та приватного права. - 2019. - Вип. 4, т. 2. - С. 50-55. - DOI: https://doi.org/10.32844/2618-1258.2019.4-2.10.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; агропромислова сфера; agro-industrial sphere; агропромышленная сфера; державне регулювання; state regulation; государственное регулирование; суб’єкт державного регулювання; subject of state regulation; субъект государственного регулирования; суб’єкт права; subject of law; субъект права; класифікація; classification; классификация; суб’єкт державного регулювання в агропромисловій сфері; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность